(Invited) Electrochemistry Meets Heterogeneous Catalysis: Solid Acid Based Electrochemical Cells Using Cu- and Pt-Based Electrodes in CO2 Containing Atmospheres. (25th June 2020) - Hallinder, Jonathan; Holtappels, Peter; Mogensen, Mogens Bjerg
Abstract : Electrochemical reactors operating at intermediate temperatures (200 – 400 °C) have the advantage that they can be thermally integrated into other chemical processes like synthesis of synthetic fuels and chemicals, such as methanol and ammonia. Electrochemical reduction of CO2 to chemical building blocks such as CO, CH3 OH, and CH4 is a dream for electrochemists, and high faradaic efficiencies have been reported for liquid electrochemical cells operated at ambient temperature, using e.g. Cu electrodes. However, selectivity and electrochemical activity are far from being technically relevant, so that heterogeneous catalysis processes still are the matter of choice. In this contribution, solid state electrochemical cells under operating conditions close to the well-known catalytic synthesis of methanol. For CO2 reduction, cells based on CsH2 PO4 as electrolyte and Cu based cathodes have been investigated towards their electrochemical activity in both H2 /H2 O and H2 /H2 O/CO2 containing atmospheres at elevated temperatures of 240 °C.